Shared Yet Contested: Energy Democracy Counter-Narratives - Burke, Matthew J. (Frontiers in Communication, 2018)
Conventional ways of communicating about the transition to renewable energy in North America presuppose that energy systems can be changed while sustaining existing social, political and economic relations. Energy democracy counters such ostensibly apolitical narratives by emphasizing the socially transformative potential of this transition. Yet energy democracy, as both organizing principle and social movement, is itself increasingly recognized as flexible and contested. This research seeks to better discern and understand the practices and implications of energy democracy and its variants through synthesis and qualitative analysis of transition counter-narratives drawn from public communications of energy democracy initiatives actively working in northeastern North America. Transition narratives are examined through four constituent elements: collective-action frames that define problems, solutions and motivations for sociotechnical change; discourses that describe values and norms of members of the communities of interest; sociotechnical imaginaries that describe and prescribe futures to be attained; and stories that connect past, present and future and identify specific agents and adversaries to change. The research finds a set of diverse organizations across the region taking up and giving shape to the concept and goals of energy democracy, revealing a convergence among these initiatives around commitments to a socially transformational shift to collectively-controlled renewable energy systems. A comparison of transition narratives suggests distinct and potentially competing approaches to energy democracy, or multiple energy democracies, described as local and regional communities, public partnerships, and social movements. These energy democracies express differences regarding social groups to be connected and empowered, theories of change and stability, form and specificity of institutional change, resistance to negative as well as promotion of positive agendas, and ability to work across scales. These differences can and perhaps must activate a productive tension among multiple energy democracies working for and within a democratized renewable energy future for this region. The paper broadly contributes to research on sustainability transitions by examining and comparing transition narratives at trans-national and sub-national levels, proposing a descriptive and analytical typology of transition counter-narratives, and initiating a data set for future research on regional social-ecological-technical systems to strengthen initiative-based practice and learning.